Intensity-difference squeezing from four-wave mixing in hot 85Rb and 87Rb atoms in single diode laser pumping system - Gisung Sim; Heewoo Kim; Han Seb Moon (Scientific Reports)
Abstract Squeezed states of light, generated through four-wave mixing (FWM), are increasingly recognized as valuable resources for various applications in quantum sensing, quantum imaging, and quantum information processing. In this study, we report achieving more than − 7.8 dB of intensity-difference squeezing (IDS) in two-mode squeezed states from hot 85Rb vapor and − 5.0 dB from hot 87Rb vapor, utilizing a fiber electro-optic modulator (EOM) within a single home-made diode laser system. By mitigating the effects of undesired multimode from the EOM on the squeezing, we experimentally demonstrated the IDS of 85Rb and 87Rb atoms within a single experimental setup, benefiting from the EOM’s ability to provide higher frequency shifts. This advancement may expand the scope of applications for hot atomic-vapor-based quantum technologies, leveraging the capabilities of the EOM.